Determinants of personal financial management practices among Malaysian youth - Rudy Ansar; Brahim Chekima; Suddin Lada; Ming Fook Lim; Mohamed Bouteraa (IDEAS, 2023)
This study examines the factors influencing personal financial management practices among Malaysian youths, with the moderating role of future orientation. This study used the theory of planned behavior as an underpinning theory to predict and understand the factors that influence personal financial management practices among Malaysian youth. The participants in the study are Malaysian individuals aged 15 to 40 years. A total of 119 valid questionnaires were collected and analyzed using structural equation modeling (SEM) with partial least squares (PLS). The data analysis findings revealed significant positive effects of financial attitude and financial literacy on the financial management practices among the Malaysian youth. Additionally, the results demonstrate that future orientation is a moderator, strengthening the associations between financial attitude, financial literacy, and personal financial management practices among young people. This study has two main implications. First, it provides valuable information for Malaysian government organizations and policymakers to develop successful plans for encouraging better financial management among young people. Furthermore, this study contributes to the extant literature on personal financial management practices by offering an alternative strategy to address the growing problem of bankruptcy among the Malaysian youth.